Clinical Practice Guidelines for the Medical and Surgical Management of Primary Intracerebral Hemorrhage in Korea - Kim, Jeong Eun; Ko, Sang-Bae; Kang, Hyun-Seung; Seo, Dae-Hee; Park, Sukh-Que; Sheen, Seung Hun; Park, Hyun Sun; Kang, Sung Don; Kim, Jae Min; Oh, Chang Wan; Hong, Keun-Sik; Yu, Kyung-Ho; et al. (Journal of Korean Neurosurgical Society, 2014)
The purpose of this clinical practice guideline (CPG) is to provide current and comprehensive recommendations for the medical and surgical management of primary intracerebral hemorrhage (ICH). Since the release of the first Korean CPGs for stroke, evidence has been accumulated in the management of ICH, such as intracranial pressure control and minimally invasive surgery, and it needs to be reflected in the updated version. The Quality Control Committee at the Korean Society of cerebrovascular Surgeons and the Writing Group at the Clinical Research Center for Stroke (CRCS) systematically reviewed relevant literature and major published guidelines between June 2007 and June 2013. Based on the published evidence, recommendations were synthesized, and the level of evidence and the grade of the recommendation were determined using the methods adapted from CRCS. A draft guideline was scrutinized by expert peer reviewers and also discussed at an expert consensus meeting until final agreement was achieved. CPGs based on scientific evidence are presented for the medical and surgical management of patients presenting with primary ICH. This CPG describes the current pertinent recommendations and suggests Korean recommendations for the medical and surgical management of a patient with primary ICH.